Projeto Formar: Apontamentos para Superação das Limitações do Estágio - RESENDE, Francisco Aparecido Holanda (Universidade Federal do Tocantins, 2024)
This work arose from observations about the limitations of curricular internships in the professional development of mathematics teachers during their initial formation in the Mathematics Teaching Program at UFNT in Araguaína. As a student of the Mathematics Program and a member of the extension project (Formar Project), which is aimed at the continued formation of teachers, it was possible to notice the training difficulties faced by teachers due to the lack of a psycho-didactic and methodological foundation in the process of initial and continued formation. These knowledge, together with the specific knowledge in the area of mathematics, are fundamental for the development of teacher professionalism. The objective of this work is to identify, analyze and expose the characteristics of curricular stage, using the concept of the School Space for Teacher Formation (EEFD), created by Romão (2022). This aims to propose theoretical-conceptual notes capable of supporting this space and helping to overcome the dichotomies that fragment teaching work and education. For this, we used bibliographic research as an investigative technique and the historical-dialetical method as a method of knowledge. Analyzing the problem, we propose the concept of praxis for the dialetical overcoming of the dichotomy between theory and practice, which together with the concept of EEFD, enable the dialetical overcoming of the existing dichotomies between teacher formation and work.